THE CRIME OF PORNOGRAPHY ON INTERNET MEDIA - Subekti; Soekorini, Noenik; Sidarta, Dudik Djaya (Lex Journal: Kajian Hukum & Keadilan, 2017)
The development of the internet gave birth to new problems. Among them appear more sophisticated crime in the form of "cybercrime". It is characterized by the rapid growth of the porn sites. The crime of pornography is often the case on the internet among other pornographic material, pornographic material have, keep pornographic material, distributing pornographic material, showing pornographic material, pornographic material lend, make yourself as an object porn, prostitution and online advertising pornographic contents. Issues to be studied in this research is how the sanctions against the crime of pornography via the Internet as well as how best to cope with the crime of pornography via the Internet. Sources of law consists of primary legal materials, including regulation, secondary law, namely literature books and journals related to the problems studied. Overall primary legal materials and secondary legal materials will be analyzed using descriptive analysis is an analytical analysis that describes or depicts nature of regulations.The results of this research are positive law in Indonesia is still inadequate or non-compliance related to the development of pornography on the internet, which limits the granting of pornography that is not clear, where the authorities to take specific actions to address the problem of pornography, the penalty is too light, obscurity party deems appropriate to account for crimes categorized as pornography. The efforts have been made but the evils of pornography is still ongoing due to the difference in interest between the interests of Internet entrepreneurs society in general, especially the lives of young people qualified in the present and the future.